2010
DOI: 10.1002/path.2749
|View full text |Cite
|
Sign up to set email alerts
|

Glial‐derived neurotrophic factor regulates intestinal epithelial barrier function and inflammation and is therapeutic for murine colitis

Abstract: Although enteric glial cells (EGCs) have been demonstrated to play a key role in maintaining intestinal epithelial barrier integrity, it is not known how EGCs regulate this integrity. We therefore hypothesized that glial-derived neurotrophic factor (GDNF) produced by EGCs might be involved in this regulation. Here we investigated the role of GDNF in regulating epithelial barrier function in vivo. Recombinant adenoviral vectors encoding GDNF (Ad-GDNF) were administered intracolonically in experimental colitis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(86 citation statements)
references
References 44 publications
3
82
1
Order By: Relevance
“…In recent years it was consistently reported, that reduced levels of GDNF lead to morphological and functional abnormalities of IEB in mice comparable to the changes known in IBD (8,61,68). Conversely, it was shown that GNDF immunoreactivity was upregulated in experimental colitis and in specimen of patients with IBD, which was an effect predominately observed in enterocytes (52).…”
Section: Gdnf Directly Promotes Barrier Maturation and Proliferation mentioning
confidence: 88%
See 1 more Smart Citation
“…In recent years it was consistently reported, that reduced levels of GDNF lead to morphological and functional abnormalities of IEB in mice comparable to the changes known in IBD (8,61,68). Conversely, it was shown that GNDF immunoreactivity was upregulated in experimental colitis and in specimen of patients with IBD, which was an effect predominately observed in enterocytes (52).…”
Section: Gdnf Directly Promotes Barrier Maturation and Proliferation mentioning
confidence: 88%
“…Zhang and coworkers (68) showed that application of recombinant adenoviral vectors encoding GDNF in a model of experimental colitis significantly reduced inflammation and loss of intestinal barrier functions. On the one hand, the underlying mechanism was attributed to anti-inflammatory effects, since GDNF blocked the secretion of various proinflammatory cytokines, such as TNF-␣ and interleukin-1␤.…”
Section: Gdnf Directly Promotes Barrier Maturation and Proliferation mentioning
confidence: 99%
“…Colonic Epithelial Barrier Function Is Preserved by AS101 Treatment-The neurotrophin, GDNF, was shown to have a central role in protecting mucosal barrier function in experimental IBD and in IBD patients via up-regulation of PI3K/AKT pathway (29,52). Previously, we showed that AS101 induces GDNF production both in vitro and in vivo (38,39).…”
Section: As101 Reduces Clinical Symptoms Of Dss-induced Murinementioning
confidence: 98%
“…GDNF was found to be upregulated both in experimental IBD and in IBD patients. GDNF has strong anti-apoptotic activities in colonic epithelial cells, which depends on activation of MAPK and PI3K/AKT pathways (29,52). One form of epithelial cell injury in inflamed colonic mucosa in ulcerative colitis is reported to involve apoptosis of these cells (67).…”
Section: Infiltration Of Cd4mentioning
confidence: 99%
“…The putative link between changes in the MPO/WBC ratio, changes in nitrotyrosine levels and reduced production of neurotrophic factors is indirectly strengthened by reports that the administration of certain neurotrophic factors prompts an improvement in several neurodegenerative disorders: Zhang et al (2010), using an experimental colitis model, found that administration of GDNF inhibited MPO activity and improved symptoms [31].…”
Section: Discussionmentioning
confidence: 96%